PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KONSENTRASI BELAJAR PADA KETERAMPILAN SENAM DONG YI GONG SISWA SMP SWASTA KOTA BEKASI - Hilman Rama Pratama; Isomudin Isomudin; Mettadewi Wong (LPSDI Bina Patria, 2025)
Hilman Rama Pratama / 2023010429 / 2024 / The Influence of Motivation and Discipline on Learning Concentration in Dong Yi Gong Exercise Skills among Private Junior High School Students in Bekasi City. Master’s Thesis in Buddhist Religious Education, Institut Nalanda. Advisor: Dr. Isomudin, S.H., M.Pd. and Dr. Mettadewi Wong, S.Ag., S.H., M.Pd.B. This study aimed to analyze the influence of motivation and discipline on students’ learning concentration in Dong Yi Gong exercise skills. Learning concentration is a key factor in educational achievement and is strongly assumed to be influenced by students’ motivation and discipline. The research employed a quantitative approach with correlational and multiple linear regression design. The sample consisted of 60 students from a private junior high school in Bekasi City, selected randomly. A validated and reliable questionnaire was used as the research instrument. Data were analyzed using correlation tests, t-tests, F-tests, and regression with the aid of SPSS. The results indicated that motivation and discipline had a positive and significant influence on learning concentration. Partially, motivation (X₁) produced the regression equation Y = 86.696 + 0.493X₁ with tcount = 15.817 > ttable = 1.672 and a simple correlation coefficient ry₁ = 0.9010. Discipline (X₂) produced the regression equation Y = 6.889 + 2.403X₂ with Fcount = 220.182 (p < 0.05) and coefficient of determination R² = 0.774. Simultaneously, motivation and discipline contributed 73.1% to learning concentration with the multiple regression equation Ŷ = 89.367 + 0.088X₁ + 0.330X₂.